REFRAMING IDENTITY AND MINORITY VOICES THROUGH COMMUNICATION PRAGMATICS IN GLOBAL–LOCAL CONTEXTS - Wahyudi Rahmat; Nor Hazwani Munirah Binti Lateh; Yohan Kurniawan (Universitas PGRI Sumatera Barat, 2025)
This article is an introduction to examining how communication pragmatics operates as a strategic resource for negotiating identity and amplifying minority voices within global–local landscapes. Drawing on a systematic review of ten empirical studies published in Volume 11, Number 2 (2025)—Autumn Issue, the study synthesizes how pragmatic practices shape meaning, power relations, and cultural positioning across diverse sociocultural settings. Rather than treating pragmatics solely as a linguistic mechanism, this review conceptualizes it as a form of cultural action through which marginalized communities preserve local values while engaging with global discourses. The analysis reveals that pragmatic strategies, such as indirectness, politeness, code-switching, ritualized speech, and digital semiotics, play a crucial role in sustaining minority identities amid pressures of standardization and globalization. Across the reviewed studies, local actors employ language performatively to assert belonging, resist erasure, and adapt to transnational norms. Examples range from sacred and customary communication practices in Minangkabau society to classroom interactions, digital communication, and intercultural encounters where global languages intersect with local epistemologies. Findings further indicate that pragmatic negotiation enables minority voices to remain audible without overt confrontation, allowing speakers to balance cultural loyalty with communicative accessibility. In educational, religious, and digital domains, pragmatic choices function as identity markers that mediate authority, solidarity, and resistance. This review highlights a recurring pattern: global communication does not simply overwrite local identities but instead generates hybrid pragmatic forms that reflect both adaptation and resilience. The study enhances the field of communication and pragmatics by showing how everyday communicative choices enact global–local dynamics. It contends that comprehending minority identity formation necessitates an examination of pragmatic practices as culturally ingrained, ideologically significant, and socially impactful. Ultimately, the article positions communication pragmatics as a key analytical lens for examining identity negotiation and minority agency in an increasingly interconnected world.